Comparison of the effects of Kinesio tape and neuromuscular electrical stimulation on hand extensors in children with cerebral palsy - Açıkbaş, Ece; Tarakcı, Devrim; Budak, Miray (Mark Allen Group, 2020)
Background/Aims Cerebral palsy is a lifelong condition resulting in weakness in the muscles, difficulty moving and excessive tension in the muscles of the arms and legs. This study aimed to investigate the effects of adding Kinesio taping and neuromuscular electrical stimulation to neurodevelopmental treatment on joint range of motion, muscle tone and functional ability in children with cerebral palsy. Methods A total of 30 children were included in the study. They were allocated to one of two groups: Kinesio taping (n=15) or neuromuscular electrical stimulation (n=15). The children in both groups received 20 sessions of twice-weekly neurodevelopmental treatment. Range of motion, Modified Ashworth Scale, Duruoz Hand Index, Manual Ability Classification System, Gross Motor Function Classification System, Minnesota Hand Skill Test and Jebsen Hand Function Test were assessed before and after the treatment programme. Results Statistically significant improvements (P<0.05) were found in all measures except Gross Motor Function Classification System in both groups. Significant between-group differences in left shoulder flexion, left shoulder abduction and unilateral Minnesota Hand Skill Test were found in favour of neuromuscular electrical stimulation; whereas significant improvement in left elbow flexion was found in favour of Kinesio taping. Conclusions The addition of Kinesio taping and neuromuscular electrical stimulation to neurodevelopmental treatment improved the joint range of motion and functional ability of children with cerebral palsy.
Keywords: Cerebral Palsy; Kinesio Taping; Neurodevelopmental Treatment; Neuromuscular Electrical Stimulation